2010
DOI: 10.1044/1092-4388(2009/07-0245)
|View full text |Cite
|
Sign up to set email alerts
|

Three Profiles of Language Abilities in Toddlers With an Expressive Vocabulary Delay: Variations on a Theme

Abstract: These results shed new light on the notion of heterogeneity in toddlers who present with an EVD by proposing subgroups among them. A follow-up investigation of these participants is ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 35 publications
4
35
0
1
Order By: Relevance
“…Some support for this possibility is provided by Desmarais et al (2010) and Bushmann et al (2008) who found that pre-schoolers with receptive delay had weaker cognitive profiles than their counterparts with expressive-only delay. However, differences in cognitive ability might be expected to have similar effects on expressive and receptive language performance.…”
Section: Discussionmentioning
confidence: 94%
“…Some support for this possibility is provided by Desmarais et al (2010) and Bushmann et al (2008) who found that pre-schoolers with receptive delay had weaker cognitive profiles than their counterparts with expressive-only delay. However, differences in cognitive ability might be expected to have similar effects on expressive and receptive language performance.…”
Section: Discussionmentioning
confidence: 94%
“…One exception is the research of Thal and colleagues (Thal, Tobias, & Morrison, 1991;Thal & Tobias, 1992) who investigated use of communicative gestures in late talkers and found an association with receptive language abilities. In line with our approach, Desmarais et al (2010) draw attention to the heterogeneity of children with early vocabulary delay and highlight the occurrence of difficulties with comprehension and engagement in communication as well as expressive language.…”
mentioning
confidence: 97%
“…A first trained research assistant interviewed the parent in charge of the child at the time of this home visit (the index parent) while a second assistant tested the child. The procedures done and the questionnaires used during this home visit have been described in a previous publication [19].…”
Section: Data Collectionmentioning
confidence: 99%
“…This instrument, commonly used in clinical settings, is designed to evaluate the communication skill of children according to their age categories. Scores were generated according to the method proposed by Desmarais et al [19]. The Bayley Scales of Infant Development (BSID-II) was administered to measure child mental and motor development [24].…”
Section: Data Collectionmentioning
confidence: 99%